TRANSPORTATION DESIGN OF NURUL KALAM GREAT MOSQUE IN PEMALANG REGENCY - Rizky Viktor Siahaan, Putra
Nurul Kalam Great Mosque is located in Pemalang District, part of northern coast of Central Jawa Province. This mosque has a total area of 16,980 square meter which has a level of four floor and one basement with a capacity of 8,000 worshipers. Aside from being a muslim place of worship, this mosque is also planned to be facility for social activities, services, sports, and tourism. Because this mosque is not only a place of worship, it is necessary to plan transportation in area of mosque so that visitors who come to the mosque using motorized vehicles can comfortably and safely when entering and exiting the mosque area. In addition, because this mosque is located in residental areas, school districts, office areass, and recreation areas, it also necessary to make an impact on the construction of mosques on condition of the surrounding traffic flow. Transportation planning progres in this mosques begins by determining the transportation modes planned to be parked and then determined the Parking Space Unit (SRP) for each mode. Next will be designed two locations of parking lots, namely parking basements and parking parks. Basemennt parking is designed as parking lot for motorbike and car, while park parking is designed as a parking lot for motorcycle, car, and bus. Next will be designed flexible pavement in parking lot, which is to determine the type and thickness of each pavement layer. Queue analysis is also carried out at each parking location to ensure that there are No. excessive queues and congestion that is constrained on the parking location. The final design process in analyzing traffic related to impact of the existence of mosque on condition of existing traffic condition around the mosque. This traffic analysis will later show changes in traffic behavior due to the increase in the flow of vehicles fromm mosques to road around mosque.